Analysis and Performance of Textile Weaving in Pakistan 2001-2010 (Global Journal of Management and Business Research, 2012)
The intention of this study is to examine and analyze the performance of Pakistani textile weaving industry over the last decade (2001-2010). This study is showing the overall performance of this sector that how much total assets are depending on equity and paid up capital. The study is examining that in which year sale is on its peak and how much sale is depending on total asset, bank chargers and profit after tax. On the other side how much profit after tax is depending on total asset, equity and sales. The study is informing about companies profit before tax and profit after tax, that how much companies are earning and how much they are giving in term of tax. This study is examining that in which years variables are more consistent. The study is analyzing that autocorrelation exists between variables or not. Overall study and its graphical representation are helping to come on a conclusion that this sector is flourishing or not, and sale and profit of the companies are increasing or decreasing over the last decade (2001-2010).
Keywords: Lacing; Yarns; Treadles; String; Looms